Magnesium metal surface treatment method, method for manufacturing battery magnesium electrode, and method for manufacturing magnesium metal secondary battery

JP2024007595A5Active Publication Date: 2025-04-07NAT INST FOR MATERIALS SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022108757
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2022-07-06
Publication Date
2025-04-07
Estimated Expiration
2042-07-06

AI Technical Summary

Technical Problem

Magnesium metal secondary batteries face challenges in maintaining electrochemical activity in dry air due to the formation of insulating films from reactions with oxygen and moisture, necessitating inert gas atmospheres for handling and manufacturing, which reduces work efficiency and increases equipment costs.

Method used

A surface treatment method for magnesium metal using a zinc compound organic solution in an aprotic organic solvent with specific ionic conductivity, forming a conductive film that maintains electrochemical activity in dry air, allowing for simplified handling and manufacturing in ambient conditions.

Benefits of technology

Enables the production of magnesium metal secondary batteries in dry air, improving work efficiency and reducing equipment needs, while maintaining electrochemical activity and enhancing productivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

To provide a magnesium metal surface treatment method capable of being handled in dry air without spoiling the electrochemical activity of magnesium metal.SOLUTION: A magnesium metal surface treatment method comprises: a pretreatment step of exposing magnesium metal on a surface of an object to be surface-treated; a surface treatment step of contacting an exposure surface of the magnesium metal to a zinc compound organic solution; and a cleaning step. The zinc compound organic solution includes a zinc compound dissolved in an aprotic organic solvent having a relative dielectric constant of more than 0 and 10 or less, and the zinc compound provides ion conductivity to the organic solution.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a magnesium metal surface treatment method, a method for producing a magnesium electrode for a battery, and a method for producing a magnesium metal secondary battery. [Background technology]

[0002] Magnesium metal secondary batteries have been attracting attention as next-generation secondary batteries, and are disclosed, for example, in Patent Document 1. This is because they have a high energy density per mass and volume, equivalent to that of lithium-ion secondary batteries, and are also superior in terms of abundance of resources, material safety compared to other materials, and material cost.

[0003] However, magnesium metal reacts with oxygen and moisture in the air to form an insulating film on its surface. For this reason, in the research and development of materials for magnesium metal secondary batteries, it was necessary to operate in an inert gas atmosphere, such as argon or nitrogen, from the storage of battery materials to the production and evaluation of the batteries. The storage and working atmosphere tolerance of battery materials has a significant impact on the battery manufacturing process. This has an impact on the feasibility of the battery, as well as the productivity of the battery. In order to control the working environment to an atmosphere composed only of argon or nitrogen, a space isolated from the outside world, such as a glove box, is necessary, which significantly reduces the work efficiency. Therefore, in order to put magnesium metal secondary batteries into practical use, a technology capable of maintaining the electrochemical activity of magnesium metal even in dry air is essential. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2014-186940 A Summary of the Invention [Problem to be solved by the invention]

[0005] An object of the present invention is to provide a magnesium metal surface treatment method that enables magnesium metal to be handled in dry air without impairing its electrochemical activity, a method for manufacturing a magnesium electrode for a battery using the surface treatment method, and a method for manufacturing a magnesium metal secondary battery. [Means for solving the problem]

[0006] The configuration of the present invention is shown below. (Configuration 1) A pretreatment step of exposing magnesium metal on the surface of the object to be surface-treated; a surface treatment step of contacting the exposed surface of the magnesium metal with an organic solution of a zinc compound; It consists of a cleaning process, The zinc compound organic solution is a solution in which a zinc compound is dissolved in an aprotic organic solvent having a relative dielectric constant of more than 0 and not more than 10, The method of claim 1, wherein the zinc compound is a zinc compound that provides ionic conductivity to the organic solution. (Configuration 2) 2. The magnesium metal surface treatment method according to claim 1, wherein the zinc compound organic solution has an ionic conductivity of 10 μS / cm or more and 50 mS / cm or less. (Configuration 3) The zinc compound is ZnR 1 R 2 (R 1 and R 2 3. The method for treating a magnesium metal surface according to claim 1 or 2, wherein the compound is at least one selected from the group consisting of zinc chloride (ZnCl2) and zinc bistrifluoromethanesulfonylamide (Zn(TFSA)2). (Configuration 4) 3. The magnesium metal surface treatment method according to claim 1, wherein the zinc compound is diethylzinc (Zn(C2H5)2). (Configuration 5) 5. The magnesium metal surface treatment method according to any one of claims 1 to 4, wherein the organic solvent is at least one selected from the group consisting of ether, hexane, chloroform, dichloromethane and tetrahydrofuran. (Configuration 6) 6. The magnesium metal surface treatment method according to any one of claims 1 to 5, wherein the content of the zinc compound in the organic solution is 0.01 mol / L or more and 1 mol / L or less. (Configuration 7) 7. The method of claim 1, wherein the pretreatment step is by polishing. (Configuration 8) 7. The magnesium metal surface treatment method according to any one of claims 1 to 6, wherein the pretreatment step is by wet etching. (Configuration 9) 9. The magnesium metal surface treatment method according to any one of claims 1 to 8, wherein the washing step is carried out with one or more selected from the group consisting of ether, hexane, chloroform, dichloromethane and tetrahydrofuran. (Configuration 10) A method for manufacturing a magnesium electrode for a battery, comprising subjecting a magnesium electrode to a surface treatment according to any one of configurations 1 to 9. (Configuration 11) 11. A method for producing a magnesium metal secondary battery, comprising the steps of: (a) preparing a magnesium electrode produced by the method according to claim 10 as a negative electrode active material and an electrode; Effect of the Invention

[0007] According to the present invention, there are provided a magnesium metal surface treatment method that enables magnesium metal to be handled in dry air without impairing its electrochemical activity, a method for manufacturing a magnesium electrode for a battery using the surface treatment method, and a method for manufacturing a magnesium metal secondary battery. This characteristic enables magnesium metal secondary batteries to be manufactured in air, greatly simplifying handling and manufacturing equipment, and greatly improving the productivity of magnesium metal secondary batteries. [Brief description of the drawings]

[0008] [Figure 1] FIG. 1 is a flow chart showing a manufacturing process of a magnesium metal electrode of the present invention. [Diagram 2]FIG. 1 is a cross-sectional view showing a schematic configuration of a magnesium metal secondary battery. [Diagram 3] FIG. 2 is an explanatory diagram illustrating an outline of an apparatus used for evaluating an electrode in the present invention. [Figure 4] 4 is a characteristic diagram showing the relationship between the voltage applied to the electrodes and the current flowing between the electrodes via the electrolyte at that time. FIG. [Diagram 5] 4 is a characteristic diagram showing the relationship between the voltage applied to the electrodes and the current flowing between the electrodes via the electrolyte at that time. FIG. [Figure 6] 4 is a characteristic diagram showing the relationship between the voltage applied to the electrodes and the current flowing between the electrodes via the electrolyte at that time. FIG. [Figure 7] 4 is a characteristic diagram showing the relationship between the voltage applied to the electrodes and the current flowing between the electrodes via the electrolyte at that time. FIG. [Figure 8] 4 is a characteristic diagram showing the relationship between the voltage applied to the electrodes and the current flowing between the electrodes via the electrolyte at that time. FIG. [Figure 9] 4 is a characteristic diagram showing the relationship between the voltage applied to the electrodes and the current flowing between the electrodes via the electrolyte at that time. FIG. [Figure 10] 4 is a characteristic diagram showing the relationship between the voltage applied to the electrodes and the current flowing between the electrodes via the electrolyte at that time. FIG. [Figure 11] 4 is a characteristic diagram showing the relationship between the voltage applied to the electrodes and the current flowing between the electrodes via the electrolyte at that time. FIG. [Figure 12] 4 is a characteristic diagram showing the relationship between the voltage applied to the electrodes and the current flowing between the electrodes via the electrolyte at that time. FIG. [Figure 13] 4 is a characteristic diagram showing the relationship between the voltage applied to the electrodes and the current flowing between the electrodes via the electrolyte at that time. FIG. [Figure 14] 4 is a characteristic diagram showing the relationship between the voltage applied to the electrodes and the current flowing between the electrodes via the electrolyte at that time. FIG. [Figure 15] 4 is a characteristic diagram showing the relationship between the voltage applied to the electrodes and the current flowing between the electrodes via the electrolyte at that time. FIG. [Figure 16] 4 is a characteristic diagram showing the relationship between the voltage applied to the electrodes and the current flowing between the electrodes via the electrolyte at that time. FIG. [Figure 17] 4 is a characteristic diagram showing the relationship between the voltage applied to the electrodes and the current flowing between the electrodes via the electrolyte at that time. FIG. [Figure 18] FIG. 1 is a characteristic diagram showing the cycle number dependency of current characteristics (slope defined by current / voltage). [Figure 19] FIG. 1 is a characteristic diagram showing the results of a constant current dissolution and deposition test. [Figure 20] FIG. 1 is a characteristic diagram showing the results of a constant current dissolution and deposition test. [Figure 21] FIG. 1 is a characteristic diagram showing the results of a constant current dissolution and deposition test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] (Embodiment 1) As shown in the flow chart of FIG. 1, the magnesium metal surface treatment method of the present invention comprises a step of preparing magnesium metal (step S11), a pretreatment step (step S12) of exposing magnesium metal on the surface of an object to be surface-treated, a surface treatment step (step S13) of contacting the exposed surface of the magnesium metal with an organic solution of a zinc compound by immersion or the like, and a cleaning step (step S14).

[0010] The magnesium metal may be in the form of either a plate or particles, but when used as a negative electrode active material for a secondary battery, the plate form is preferred from the viewpoint of workability.

[0011] Examples of pretreatment steps for exposing magnesium metal include polishing such as sandblasting, wet etching, sputtering, and ion milling. Among these, polishing and wet etching are particularly preferred from the viewpoints of cost and ease of handling.

[0012] The zinc compound organic solution is a solution in which a zinc compound is dissolved in an aprotic organic solvent with a relative dielectric constant greater than 0 and not exceeding 10, and the zinc compound is a zinc compound that imparts ionic conductivity to the organic solution. Aprotic organic solvents with a relative dielectric constant within this range are preferred because they are less likely to cause side reactions with magnesium metal and cause less decrease in activity of magnesium metal.

[0013] The zinc compound is ZnR 1 R 2 (R 1 and R 2 One or more selected from the group consisting of ZnCl2 (zinc chloride) and Zn(TFSA)2 (zinc bistrifluoromethanesulfonylamide) are preferred as treatment materials for ensuring electrochemical activity of the magnesium metal surface. A particularly preferred zinc compound is diethylzinc (Zn(C2H5)2). As demonstrated in the examples, diethylzinc can provide magnesium metal for negative electrode active material with electrochemical properties equivalent to those obtained when treated under an inert argon atmosphere.

[0014] The organic solvent may be, for example, one or more selected from the group consisting of ether, hexane, chloroform, dichloromethane, and tetrahydrofuran. These materials are easy to handle and have high solubility for zinc compounds, and are therefore preferably used.

[0015] The content of the zinc compound in these organic solutions is preferably 0.01 mol / L or more and 1 mol / L or less. By making it 0.01 mol / L or more, there is an effect of promoting the surface reaction, and by making it 1 mol / L or less, it becomes easy to suppress the generation of precipitation and foreign matter. The ionic conductivity of the solution is preferably 10 μS / cm or more and 50 mS / cm or less. If it is 10 μS / cm or more, there is an effect of promoting the surface reaction. There is no particular upper limit as long as one or more organic solvents selected from the group consisting of ether, hexane, chloroform, dichloromethane, and tetrahydrofuran are used, but for solutions containing other materials, since it is an organic solvent, 50 mS / cm or less is the practical upper limit.

[0016] The washing step is preferably performed with a washing solution selected from the group consisting of ether, hexane, chloroform, dichloromethane and tetrahydrofuran. These washing solutions are easy to handle, have high cleaning power and are unlikely to leave contaminants or foreign matter on the magnesium metal surface. If washing is performed using these washing solutions, sufficient electrochemical dissolution and deposition activity can be obtained.

[0017] With the above structure, magnesium ions are conductive while blocking oxygen. Therefore, when magnesium metal is subjected to the surface treatment of the present invention, a coating made of zinc and magnesium is formed on the surface, enabling the metal to retain its activity even in dry air.

[0018] By subjecting magnesium metal to the above surface treatment in the manufacturing process of magnesium electrodes, magnesium electrodes can be manufactured in a dry air environment, which dramatically improves workability and greatly reduces investment in facilities and the environment.

[0019] In the manufacture of magnesium metal secondary batteries, when magnesium metal produced by applying the surface treatment method of the present invention is used, the magnesium metal secondary batteries can be manufactured in dry air, which greatly simplifies handling and manufacturing equipment, and greatly improves the productivity of magnesium metal secondary batteries.

[0020] As shown in FIG. 2, the magnesium metal secondary battery 101 mainly comprises a positive electrode active material 21 and a positive electrode current collector 22 which constitute the positive electrode, a negative electrode active material 23 and a negative electrode current collector 24 which constitute the negative electrode, a separator 25, and an electrolyte 26, and these parts are generally packaged in a housing (not shown).

[0021] When the magnesium metal electrode is subjected to the above surface treatment, the magnesium metal electrode maintains its electrochemical activity even when handled in dry air. This allows the manufacturing process of the electrodes, particularly the negative electrode active material 23, and the assembly process of the positive electrode active material 21, the positive electrode current collector 22, the negative electrode active material 23, the negative electrode current collector 24, the separator 25, and the electrolyte 26 into a case to be carried out in a dry air environment rather than a vacuum or inert gas environment, greatly improving the productivity of the magnesium metal secondary battery 101. EXAMPLES

[0022] Example 1 <Sample preparation> First, a magnesium metal plate (manufactured by Nilaco) was prepared. The purity of the magnesium metal was 99.9%. Next, the prepared magnesium metal plate was placed in a 0.1 mol / dm 3 The specimen was immersed in a diethylzinc (Zn(C2H5)2) / ethylene glycol dimethyl ether solution prepared as described above for 1 hour. After 1 hour, the magnesium metal plate was removed from the solution, the solution remaining on the surface was washed off with tetrahydrofuran, and then it was dried at room temperature to obtain a surface-treated magnesium metal plate. Here, the ionic conductivity of the diethylzinc (Zn(C2H5)2) / ethylene glycol dimethyl ether solution was 12 μS / cm, and the relative dielectric constant of ethylene glycol dimethyl ether was 7.2.

[0023] <Evaluation> The above surface-treated magnesium metal plate was used as the working electrode 35, the coil-shaped platinum wire was used as the counter electrode 34, and the silver wire was used as the reference electrode 33. 3A three-electrode beaker cell 102 containing the tetrakis(hexafluoroisopropoxyl)aluminate / diethylene glycol dimethyl ether solution (Mg[Al(HFIP)4]2 / G2) prepared in the above as the electrolyte 31 was used in dry air (dew point -79.8°C) (see Fig. 3), and the electrochemical dissolution-deposition activity was evaluated by cyclic voltammetry. The voltage application rate was 10 mV / s, and the environmental temperature was 30°C. As a result, as shown in Figure 4, a current response corresponding to the electrochemical dissolution and deposition of magnesium was confirmed even in dry air. Figures 4(a) to (d) show the measurement data at 1, 10, 50, and 100 cycles, respectively. As the number of cycles increases, the slope of the curve indicating the potential chemical activity as a battery electrode becomes gentler and the current response weakens, but since the environment in which this electrode is used in secondary batteries is a sealed environment, this is an over-specified evaluation, and it is still fully practical. Based on experience, if a current response is confirmed after 10 cycles, the electrode has sufficient electrochemical activity as a secondary battery electrode.

[0024] Example 2 In Example 2, the electrode was electrochemically evaluated in the same manner as in Example 1, except that diethyl zinc was replaced with zinc chloride (ZnCl2). Here, the ionic conductivity of the ZnCl2 / ethylene glycol dimethyl ether solution was 57 μS / cm. The results are shown in Figure 5. Even after 10 cycles, there was a sufficient slope, indicating that the electrode had sufficient electrochemical activity as an electrode for a secondary battery.

[0025] Example 3 In Example 3, the electrode was electrochemically evaluated in the same manner as in Example 1, except that diethyl zinc was replaced with bis(trifluoromethanesulfonyl)zinc (Zn(TFSA)2). Here, the ionic conductivity of the Zn(TFSA)2 / ethylene glycol dimethyl ether solution was 98 μS / cm. The results are shown in FIG. 6. Even after 10 cycles, the electrode had a valid slope, indicating that the electrode had sufficient electrochemical activity as an electrode for a secondary battery.

[0026] (Reference example 1) In Reference Example 1, a magnesium metal plate similar to that in Example 1 was prepared, and the electrochemical activity evaluation was performed on this sample in an argon atmosphere in a glove box without metal surface pretreatment, similar to that in Example 1. The results are shown in Figure 7. Although the sample has sufficient electrochemical activity as an electrode for a secondary battery, the characteristic curve shows little significant difference from the results of the diethylzinc (Zn(C2H5)2) / ethylene glycol dimethyl ether solution treatment in Example 1, at least up to 10 cycles.

[0027] Comparative Example 1 In Comparative Example 1, a magnesium metal plate similar to that in Example 1 was prepared, and the electrochemical activity of this sample was evaluated in the same manner as in Example 1, without pretreatment of the metal surface, under dry air similar to that in Example 1. The results are shown in FIG. As a result, in Comparative Example 1, no significant slope was observed in the characteristic curve, and sufficient electrochemical activity as an electrode for a secondary battery, i.e., no current response corresponding to magnesium dissolution and precipitation, was observed, indicating that the moisture and oxygen blocking ability was nonexistent or extremely small.

[0028] Comparative Example 2 In Comparative Example 2, the electrode was electrochemically evaluated in the same manner as in Example 1, except that diethyl zinc was replaced with diphenyl zinc (Zn(Ph)2). Here, the ionic conductivity of the Zn(Ph)2 / ethylene glycol dimethyl ether solution was 77 μS / cm. The results are shown in FIG. As a result, no significant slope was observed in the characteristic curve, and sufficient electrochemical activity as an electrode for a secondary battery, i.e., no current response corresponding to magnesium dissolution and deposition, was observed, indicating that these coatings have no or very little moisture and oxygen blocking ability. The slope of the characteristic curves when treated with each solution containing Zn versus the number of cycles is shown in Figure 18. Note that for Zn(C2H5)2, discontinuities were observed at 50 and 51 cycles, which is thought to be due to the interval between measurements.

[0029] Comparative Example 3 In the same manner as in Example 1, 3 Solutions were prepared by dissolving normal butyl lithium, calcium borohydride, trimethylaluminum, triphenyl bismuth, tetramethyl germanium, bis(cyclopentadienyl) manganese, tetramethyl tin, and ethyl magnesium chloride in ethylene glycol dimethyl ether, and a magnesium metal plate was immersed in each solution for 1 hour. Here, normal butyl lithium, calcium borohydride, trimethylaluminum, triphenyl bismuth, tetramethyl germanium, bis(cyclopentadienyl) manganese, and tetramethyl tin ethyl magnesium chloride are positioned as representatives of Li, Ca, Al, Bi, Ge, Mn, and Sn solutions, respectively. Then, the electrochemical dissolution / deposition activity was evaluated by cyclic voltammetry using a three-electrode beaker cell 102 in the same manner as in Example 1 except that the above solution was changed. As a result, when a magnesium metal plate treated with a Li / Ca / Al / Bi / Ge / Mn / Sn solution was used as the working electrode, no current response corresponding to magnesium dissolution and deposition was observed, as shown in Figures 10 to 16, indicating that these coatings have no or very little moisture and oxygen blocking ability.

[0030] Comparative Example 4 In Comparative Example 4, a plate-shaped Mg-Al-Zn alloy was prepared, and the electrochemical activity of this sample was evaluated in the same manner as in Example 1, without metal surface pretreatment, in dry air as in Comparative Example 1. The Mg-Al-Zn alloy is an alloy composed of 96% Mg, 3% Al, and 1% Zn in terms of element ratio. The results are shown in FIG. 17. In Comparative Example 4, no significant slope was observed in the characteristic curve, and sufficient electrochemical activity as an electrode for a secondary battery, i.e., no current response corresponding to magnesium dissolution and precipitation, was observed, indicating that the moisture and oxygen blocking ability was nonexistent or extremely small.

[0031] Example 5 In Example 5, a magnesium metal secondary battery was fabricated using the magnesium metal electrode processed and fabricated in Example 1 as the negative electrode (negative electrode active material 23), and its electrical characteristics were evaluated. Here, copper foil was used as the positive electrode active material 21, stainless steel was used as the negative electrode current collector 24, aluminum was used as the positive electrode current collector 22, and 0.3 mol / dm 3 The battery was prepared using a tetrakis(hexafluoroisopropoxyl)aluminate / diethylene glycol dimethyl ether solution (Mg[Al(HFIP)4]2 / G2) prepared as described above, and a glass filter was used as a separator. This evaluation was performed in a closed system, and the battery was prepared in dry air, but only the oxygen enclosed in the battery had an effect during operation. A constant current deposition and dissolution evaluation test was carried out under the conditions of a current density of 1 mA / cm 2 , charge per cycle / h 0.5mAh / cm 2 , and the number of cycles was 300. The change in voltage over time during cyclic operation is shown in Figures 19 and 20. Here, Figure 19 shows the voltage change over 300 cycles, i.e., 300 hours, and Figure 20 shows the voltage change over 10 hours, from 100 hours to 110 hours. In Example 5, diethyl zinc, which is an organic zinc, is used as a zinc compound for the surface treatment of the magnesium metal negative electrode active material, and good operation is observed.

[0032] Comparative Example 5 In Comparative Example 5, a magnesium metal secondary battery was fabricated using the magnesium metal electrode fabricated in Comparative Example 1 as the negative electrode (negative electrode active material 23), and its electrical characteristics were evaluated. That is, in the case of using negative electrode active material 23 fabricated in dry air without metal surface pretreatment, evaluation was performed in accordance with Example 5 except for negative electrode active material 23. The results are shown in Figure 21. The untreated sample without metal surface pretreatment had a high overvoltage for causing Mg precipitation and dissolution, and the voltage regulation value was immediately reached and the next cycle was started repeatedly, with the measurement of 300 cycles being completed within 0.05 hours, indicating that the sample was inactive. [Industrial Applicability]

[0033] As described above, the present invention enables magnesium metal secondary batteries to be manufactured in air, greatly simplifying handling and manufacturing equipment, and greatly improving productivity of magnesium metal secondary batteries. Magnesium metal secondary batteries have an energy density as high as that of lithium-ion secondary batteries, and are excellent in terms of resource abundance, material safety compared to other materials, and material costs, making them a promising secondary battery with a promising future. High energy density secondary batteries are positioned as essential devices, equipment, and facilities for realizing a smart society, and we believe that the present invention will have a major impact on society and also have a significant influence on industry. [Explanation of symbols]

[0034] 21 Cathode active material 22 Positive electrode current collector 23 Negative electrode active material 24 Negative electrode current collector 25 Separator 26 Electrolytes 31 Electrolytes 32 Container 33 Positive electrode (working electrode) 34 Negative electrode (counter electrode) 35 Reference pole 36 Variable voltage power supply 37 Ammeter 38 Voltmeter 101 Magnesium metal secondary battery 102 Three-electrode beaker cell

Claims

1. A pretreatment step of exposing magnesium metal on the surface of the object to be surface-treated; a surface treatment step of contacting the exposed surface of the magnesium metal with an organic solution of a zinc compound; It consists of a cleaning process, The zinc compound organic solution is a solution in which a zinc compound is dissolved in an aprotic organic solvent having a relative dielectric constant of more than 0 and not more than 10, The method of claim 1, wherein the zinc compound is a zinc compound that provides ionic conductivity to the organic solution.

2. 2. The method for surface treatment of magnesium metal according to claim 1, wherein the ionic conductivity of the zinc compound organic solution is 10 μS / cm or more and 50 mS / cm or less.

3. The zinc compound is ZnR 1 R 2 (R 1 and R 2 represents an alkyl group), zinc chloride (ZnCl 2 ) and zinc bistrifluoromethanesulfonylamide (Zn(TFSA) 2 3. The method for treating a magnesium metal surface according to claim 1, wherein the surface treatment is carried out using one or more of the following:

4. The zinc compound is diethylzinc (Zn(C 2 H 5 ) 2 3. The method for treating a magnesium metal surface according to claim 1 or 2, comprising the steps of:

5. 2. The magnesium metal surface treatment method according to claim 1, wherein the organic solvent is at least one selected from the group consisting of ether, hexane, chloroform, dichloromethane and tetrahydrofuran.

6. 2. The magnesium metal surface treatment method according to claim 1, wherein the content of the zinc compound in the organic solution is 0.01 mol / L or more and 1 mol / L or less.

7. 2. The method of claim 1, wherein the pretreatment step is by polishing.

8. 2. The method of claim 1, wherein the pretreatment step is by wet etching.

9. 2. The magnesium metal surface treatment method according to claim 1, wherein the washing step is performed with one or more selected from the group consisting of ether, hexane, chloroform, dichloromethane and tetrahydrofuran.

10. A method for producing a magnesium electrode for a battery, comprising subjecting a magnesium electrode to the surface treatment according to claim 1.

11. A method for producing a magnesium metal secondary battery, comprising using a magnesium electrode produced by the method according to claim 10 as a negative electrode active material and electrode.